Study on Performance of R417A Heat Pump Water Heater and Heat Transfer of Spiral Tube Condenser - Zhang Xiaoyan; Xia Xiang (Zhileng xuebao)
In the study, the operation performance of air source heat pump water heater and heat transfer performance of spiral casing condenser were examined by using R417A as a refrigerant. The experimental conditions are as follows: inlet water temperature of the condenser is 20–55 ℃, influent flow rate of the condenser is 0.6–1.0 m3/h, and environmental temperatures are 15 ℃ and 29 ℃. The experimental results indicate that when the water flow is constant, increases in the entrance temperature result in the decrease in the total heat transfer rate and total heat transfer coefficient of performance (COP), the increase in the discharge pressure and input power of the compressor, and the decrease in the heating capacity and heating coefficient of the heat pump water heater. When the condenser entrance water temperature is constant, with increases in the water flow, the total heat transfer rate and the total heat transfer coefficient are increased, discharge pressure and the input power of the compressor are reduced, and heating capacity and heating COP of the heat pump water heater are increased. When the ambient temperature is 29 ℃, total heat transfer, total heat transfer coefficient, exhaust pressure, suction pressure, input power, heating capacity, and heating COP of the condenser exceed those when the ambient temperature is 15 ℃.